1997
DOI: 10.1073/pnas.94.23.12390
|View full text |Cite
|
Sign up to set email alerts
|

The amphiphysin-like protein 1 (ALP1) interacts functionally with the cABL tyrosine kinase and may play a role in cytoskeletal regulation

Abstract: ABSTRACTcABL is a protooncogene, activated in a subset of human leukemias, whose protein product is a nonreceptor tyrosine kinase of unknown function. cABL has a complex structure that includes several domains and motifs found in proteins implicated in signal transduction pathways. An approach to elucidate cABL function is to identify proteins that interact directly with cABL and that may serve as regulators or effectors of its activity. To this end, a proteininteraction screen of a phage expression library wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 53 publications
2
56
0
Order By: Relevance
“…The Drosophila homologue of mammalian Abl, D-Abl, is also responsible for regulating actin dynamics and cell adhesion of neurons (5,49,50). This is consistent with observations that ablϪ/Ϫ argϪ/Ϫ mice show lethal defects in neurulation and changes in their actin cytoskeleton (3).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The Drosophila homologue of mammalian Abl, D-Abl, is also responsible for regulating actin dynamics and cell adhesion of neurons (5,49,50). This is consistent with observations that ablϪ/Ϫ argϪ/Ϫ mice show lethal defects in neurulation and changes in their actin cytoskeleton (3).…”
Section: Discussionsupporting
confidence: 75%
“…Recent evidence suggests that Abl family kinases regulate the actin cytoskeleton and influence cell morphology (2)(3)(4)(5)(6)(7)(8). However, the biological significance of this is not clear.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…A very recent study reported an interaction between the tyrosine kinase c-Abl and ALP-1, an Amph2 splice variant with a broad tissue distribution 49 . The interaction occurs through the SH3 domain of ALP-1.…”
Section: Reviewmentioning
confidence: 99%
“…For example, several endocytosis proteins such as Eps15, CALM/AP180, and endophilins such as SH3p8 have been translocation partners of MLL [162]. In addition, splice variants of amphiphysin can interact with c-abl or myc to enhance their transforming activities [163,164] and can also be a tumour-associated (paraneoplastic) autoantigen [165]. Adaptins have also been reported to be deleted in some tumours [166]; the TSC2 gene (responsible for tuberous sclerosis) is a biochemical and functional partner of Rab5, a GTPase involved in the endocytic pathway [167]; and β-adaptin is reported to bind a cancer critical gene, ATM [168].…”
Section: Septins and Neoplasiamentioning
confidence: 99%